[OP.6A.05] CARDIOVASCULAR DISEASE RISK FACTORS IN ADOLESCENT STUDENTS FROM A BRAZILIAN STATE CAPITAL. (September 2016) - Jardim, T.; Nascente, F.; Peixoto, M.; Carneiro, C.; Medonça, K.; Póvoa, T.; Sousa, A.; Barroso, W.; Shimizu, H.; Jardim, P.
Abstract : Objective: To determine the prevalence of cardiovascular disease risk factors in adolescents from public and private schools of a Brazilian state capital. Design and method: Cross-sectional study with a representative sample of adolescents aged 14 to 18 years, enrolled in public and private schools in Goiânia, Goiás state, Brazil. The data collection included a standard questionnaire (gender, age, ethnicity, smoking, alcohol consumption in the last 30 days, socioeconomic status, and family history of cardiovascular disease); the International Physical Activity Questionnaire (IPAQ); and a physical assessment (weight, height, waist circumference, and blood pressure). The prevalence ratio was used as the measure of association, estimated by Poisson regression. Results: The sample was composed of 862 adolescents with a mean age of 15.4 ± 1.1 years and with a predominance of females (52.8%). Alcohol consumption in the last 30 days (72.2%) and physical inactivity (66.8%) were the most prevalent cardiovascular risk factors. The most prevalent variables in female adolescents were socioeconomic class C (53.6%; p = 0.022), alcohol consumption in the last 30 days (75.4%; p = 0.025) and physical inactivity (66.8%, p = 0.000). In male adolescents, the most prevalent variables were abnormal blood pressure (24.3%; p = 0.000), abnormal waist circumference (17.2%; p = 0.011), and overweight (24.6%; p = 0.001). The prevalence of a family history of cardiovascular disease was 39.5%. Most adolescents (60.3%) had three or more risk factors, and only 1.1% did not present any cardiovascular risk factor. Conclusions: The prevalence of cardiovascular disease risk factors, particularly the occurrence of multiple risk factors, was high in the population studied.